EFFECT OF PROFITABILITY, FIRM SIZE, AND LEVERAGE ON CASH HOLDING IN MANUFACTURING COMPANIES - Garletta Delia Hankho; Elizabeth S Dermawan; MF. Djeni Indrajati (Universitas Kristen Krida Wacana, 2020)
The purpose of this empirical research is to examine about the effect of profitability, firm size, and leverage on cash holding in manufacturing companies listed on the Indonesia Stock Exchange from 2015 to 2017. The research used 67 manufacturing companies that were selected using purposive sampling method for a total of 201 data in three years. Data processing technique using multiple regression analysis with SPSS version 24.0 . The results of this research shows that all independent variables have influence on cash holding simultaneously. The partially test showed that profitability have positive and significant influence on cash holding, firm size does not significantly influence cash holding, and leverage have negative and significant influence on cash holding. Keywords:cash holding, profitability, firm size, leverage